In the mix: the potential benefits of adding GM-CSF to CpG-B in the local treatment of patients with early-stage melanoma. (1st January 2020) - Koster, Bas D.; de Jong, Tamarah D.; van den Hout, Mari F. C. M.; Sluijter, Berbel J. R.; Vuylsteke, Ronald J. C. L. M.; Molenkamp, Barbara G.; Vosslamber, Saskia; van den Tol, M. Petrousjka; van den Eertwegh, Alfons J. M.; de Gruijl, Tanja D.
ABSTRACT: Whereas TLR9 agonists are recognized as powerful stimulators of antitumor immunity, GM-CSF has had mixed reviews. In previously reported randomized trials we assessed the effects of local immune modulation in early-stage melanoma with CpG-B alone or with GM-CSF. Here we discuss the added value of GM-CSF and show sex-related differences.